Quantitative Proteomic Analysis of Global Protein Acetylation in PRRSV‐Infected Pulmonary Alveolar Macrophages. Issue 2 (21st December 2020) - Fang, Jianyu; Qiao, Songlin; Wang, Keling; Li, Rui; Wang, Lei; Li, Haili; Zhang, Gaiping
Abstract: Porcine reproductive and respiratory syndrome (PRRS), caused by PRRS virus (PRRSV), is a serious viral disease affecting global swine industry. Due to the lack of effective vaccines, new antiviral strategies to compensate for the inefficacy of available vaccines are urgently required. Lysine acetylation, as an important post‐translational modification during infection, plays a key regulatory role in host antiviral responses. In this study, the global acetylome is profiled using acetylation specific antibody‐based enrichment and tandem mass tag label high‐affinity purification liquid chromatography‐mass spectrometry in PRRSV‐infected pulmonary alveolar macrophages (PAMs). As a result, 3731 lysine acetylation sites on 1421 cellular proteins are identified. Bioinformatics analysis of the different acetylated proteins revealed their involvement in various biological processes, including the host immune response and energy metabolism. These findings will contribute to the understanding of PRRSV pathogenesis and identify new cellular targets for anti‐PPRSV therapeutics.